(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Here large data is introduced to improve the technology in computer science. This data is described as big data which is accessed by using internet. In this paper the development of big data is presented using software testing technology. This system will determine the quality, stability and reliability of the system. High performance is obtained in the system by determining the big data analysis. There is a need to develop a testing framework which is application independent and scalable with the increased requirements of each application. Hence the proposed system gives effective result in terms of reliability and quality